Keterlambatan Berbahasa dalam Aspek Fonologi pada Anak Usia 5 Tahun - Risky Nur Amalia; Farida Maesaroh (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this study was to find out the causes of language delays in phonological aspects of five-year-old subjects. The problem that underlies this research is related to language disorders. Language disorder in children's speech development is one type of communication disorder which is indicated for children who experience disturbances in the process of using any symbols in language. In this study, it discusses speech sound pronunciation disorders experienced by 5 year old children, especially in the phonological aspect. The method used is qualitative with note-taking techniques and collecting data sources through interviews, subjects are given light questions so they are easy to understand.